AN ANALISYS OF METHAFOR OF MODALITY IN THE THIRBUSH-KERRY PRESIDENTAL DEBATE - Meri Permatahati, - (2008)
ABSTRACT The present study is entitled An Analysis of Metaphor of Modality in the Third Bush-Kerry Presidential Debate. This study aims to find the types and values of metaphor of modality that were used by Kerry and Bush and to identify how the use of metaphor of modality reveals the speakers' explicitness in expressing their positions. The present study is largely qualitative; however, some descriptive quantification is also employed. The data obtained from the transcript of the debate was taken from http://www.debates.org/pages/trans2004d.html. This study examines the data by using three analysis stages of CDA proposed by Fairclough (1989) namely description, interpretation and explanation. The analysis focuses on the use of metaphor of modality in terms of its types and values by using Hallidayan theory as the tool. The results show that the metaphor of modality in the debate occur in form of probability and obligation within three value systems namely high, median and low. Moreover, the use of metaphor of modality can reveal the explicitness of the speakers in expressing their position. The more the speakers use the metaphor of modality, the more explicit they are. In the debate, Kerry used the metaphor of modality more than bush did. It shows that Kerry was less certain of what he said.